Pengaruh Konflik Kerja, Workload dan Stres Kerja Terhadap Work Motivation - Nada, Jihan Rofila Qotrun; Andriani, Dewi; Firdaus, Vera (Universitas Islam Kadiri, 2024)
This research discusses the influence of work conflict, workload, work stress, on work motivation of Medical Personnel at the Wonoayu Health Center. This research aims to determine the relationship between each independent variable and the dependent variable. The research method uses quantitative by sending questionnaires directly to each prospective respondent to collect data. The data used were respondents from Medical Personnel at the Tarik Health Center Wonoayu personnel totaling 100 employees. Data analysis technique is multiple linear regression using the help of SPSS 24 (Statistical Program For the Social Sciences) software program to test research data. The results explained that work conflict influences work motivation, workload influences work motivation, work stress influences work motivation.